Study on Mechanism of Structure Angle on Microstructure and Properties of SLM-Fabricated 316L Stainless Steel - Li, Xiaofeng; Yi, Denghao; Wu, Xiaoyu; Zhang, Jinfang; Yang, Xiaohui; Zhao, Zixuan; Wang, Jianhong; Liu, Bin; Bai, Peikang (Frontiers in Bioengineering and Biotechnology, 2021)
In this study, seven 316L stainless-steel (316L SS) bulks with different angles (0°, 15°, 30°, 45°, 60°, 75°, and 90°) relative to build substrate were built via selective laser melting (SLM). The influences of different angles on the metallography, microstructure evolution, tensile properties, and corrosion resistance of 316L SS were studied. The 0° sample showed the morphology of corrugated columnar grains, while the 90° sample exhibited equiaxed grains, but with a strong <101> texture. The 60° sample had a good strength and plasticity: the tensile strength with 708 MPa, the yield strength with 588 MPa, and the elongation with 54.51%. The dislocation strengthening and grain refinement play a vital role in mechanical property for different anisotropy of the SLM-fabricated 316L SS. The 90° sample had greater toughness and corrosion resistance, owe to the higher volume fraction of low-angle grain boundaries and finer grains.